EXPLORATION OF ORIGINAL SCIENCE (INDEGENOUS SCIENCE) SALT FARMERS IN THE TRADITIONAL SALT PRODUCTION AS A RELIABLE EFFECT OF CHEMICAL LARGE BASED MATERIALS - Hidayah, Fitria Fatichatul; Yuliyanto, Eko; Imaduddin, Muhamad (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
One of the concepts of indigenous science that can be explored is local knowledge of traditional salt production. This study aims to describe the condition of indigenous science of Central Java salt farmers in the salt production process. The design of this research is survey and descriptive research. This research uses qualitative research approach through ethnosains.The background of this research is salt farming area located in two regencies in Central Java, namely Jepara and Pati districts. This research is a qualitative research. Researchers in this study relate to several key informants (key person) and other informants and involve respondents and research participants. The next informant was determined based on the instruction of the selected key informant using purposive and snowball sampling principles.The process of data analysis in this study is done simultaneously and cyclic with the data collection process. It also uses data triangulation techniques through analysis of several data sources be it primary or secondary data. The result of this research is document of indegenousscience condition of farmer daram in traditional salt production process. Furthermore, the document can be developed into teaching materials based on local wisdom.Key words: local wisdom, indegeneous science, salt farmers, teaching  materials